Peningkatan Hasil Belajar Ilmu Pengetahuan Alam Materi Posisi Dan Bayangan Matahari Siswa Kelas II Melalui Model Pembelajaran Kooperatif Tipe Picture and Picture - Hermawan, Cecep Maman; Umaliah, Hiffatul; Febriansyah, Vicky; Angellika, Putri; Rahayu, Lisda; Rosfiani, Okta (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Picture and picture is a cooperative learning model that supports cooperation by involving image media that are sorted and paired into a logical sequence. The aim of this research is to determine the improvement in Natural Sciences (IPA) learning outcomes regarding the position and shadow of the sun through the picture and picture type cooperative learning model for class II students at SDN Tanjung Barat 09. This research uses a mixed approach, with a Classroom Action Research design consists of pre-cycle, cycle I, cycle II. The participants who took action were the class teacher and class II students at SDN Tanjung Barat 09, totaling 26 students. The implementation procedure refers to the model developed by Kemmis and MC Taggart where the cycle consists of four stages, namely: planning, implementation, observation and reflection. The data collection techniques used in this research are: observation, field notes, tests, and documents. This research begins with the pre-cycle stage, where students still experience difficulties in studying science material regarding the position and shadow of the sun with a completion percentage of 42.30%. From the Pre-Cycle results, there were 26 students who took part in the learning. The highest score was 90 and the lowest score was 40. Meanwhile, the results of Cycle 1 can be proven by an increase in the average score of 74.38 in Cycle I, to 78.7 and in the results of Cycle II with a presentation completion reached 80.80% from previously only 65.40%. By using the right learning model, Natural Science (Science) lessons become more enjoyable. Based on the research results above, it can be concluded that the picture and picture type cooperative learning model can improve the learning outcomes of class II students and raise students' enthusiasm and motivation in the learning process.